2022
DOI: 10.3390/cancers14030683
|View full text |Cite
|
Sign up to set email alerts
|

Chrysanthemum morifolium Extract Ameliorates Doxorubicin-Induced Cardiotoxicity by Decreasing Apoptosis

Abstract: It is well known that the anthracycline anticancer drug doxorubicin (DOX) induces cardiotoxicity. Recently, Chrysanthemum morifolium extract (CME), an extract of the purple chrysanthemum flower, has been reported to possess various physiological activities such as antioxidant and anti-inflammatory effects. However, its effect on DOX-induced cardiotoxicity is still unknown. An 3-(4,5-Dimethylthiazol-2-yl)-2,5-Diphenyltetrazolium Bromide (MTT)assay revealed that 1 mg/mL of CME reduced DOX-induced cytotoxicity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 47 publications
0
0
0
Order By: Relevance
“…The bioactive compounds isolated from Chrysanthemum morifolium include flavonoids, phenolic acids, anthraquinones, polysaccharides, and terpenoids [2]. According to previous investigations, the potential health benefits of Chrysanthemum morifolium may include, but are not limited to, antioxidant [3][4][5], anti-inflammatory [2,6,7], hypolipidemic effects [8], and anti-carcinogenesis activities [9,10], as well as cardiovascular protection [11,12]. Li, et al [6] reported that Chrysanthemum morifolium extract (CME) inhibited lipopolysaccharide-induced increases in IL6 and IL1β mRNA levels, as well as H 2 O 2 -induced reactive oxygen species (ROS) production in cultured cells.…”
Section: Introductionmentioning
confidence: 99%
“…The bioactive compounds isolated from Chrysanthemum morifolium include flavonoids, phenolic acids, anthraquinones, polysaccharides, and terpenoids [2]. According to previous investigations, the potential health benefits of Chrysanthemum morifolium may include, but are not limited to, antioxidant [3][4][5], anti-inflammatory [2,6,7], hypolipidemic effects [8], and anti-carcinogenesis activities [9,10], as well as cardiovascular protection [11,12]. Li, et al [6] reported that Chrysanthemum morifolium extract (CME) inhibited lipopolysaccharide-induced increases in IL6 and IL1β mRNA levels, as well as H 2 O 2 -induced reactive oxygen species (ROS) production in cultured cells.…”
Section: Introductionmentioning
confidence: 99%